THE USE OF BALIPLUS MINERAL FERTILIZER TO INCREASE PRODUCTION AND FARM INCOME OF Phaseolus vulgaris L. (Case Study in Andisol, Baturiti Tabanan Bali) - Lanya, Indayati; Subadiyasa, Nengah Netera (International Journal of Biosciences and Biotechnology; Vol 5 No 2 (2018), 2018)
Increased production of foodstuffs is required in line with increasing population. The tourism sector in Bali needs quality products that are both viable and environmentally friendly. Previous research since 2002-2016, found mineral fertilizer plus can increase the highest production, , increased soil quality, and increased farm income. The research location was in Baturiti Subdistrict. The plant tested was string bean (Phaseolus vulgaris L) during first planting and residual effect of first fertilization (second planting). Eight fertilizer treatments: P0=control, P1=organic, P2= mineral, P3=chemical (NPK), P4=combination ½ (organic+chemical), P5=combination ½ (mineral+chemical), P6= Baliplus mineral fertilizer (BMF) =combination ½ (organic+mineral+chemical), and P7=combination ½(organic+mineral)], three replications. Parameters observed were bean weight, storage capacity, and value of farm income. The experimental designed used was Randomized Block Design, with Duncan's real test difference of 5%, using the Costat program. Fertilization was very influential and significantly affected to the production of the first planting and residual effects. The treatment using BMF in the first crop,resulted in the highest production (34.33 tons ha-1), highest production increase (62.92%), longest storage (36%) for one week, and the highest farm income (Rp 334 million ha-1). The P1 treatment showed the lowest production (25 ton ha-1), the lowest increase (18.45%), storage capacity (15.27%), and the lowest farm income (Rp 28.7 million ha-1). String bean with the highest residual effect (16.17 ton ha-1) was obtained in treatment P4. The average production of the remaining effect is 48.62% of the first crop. The use of mineral fertilizers plus bali can increase production, savings, and farm income, and reduce 50% of the use of chemical and organic fertilizers.